Measurement of Radon Levels in Dwellings in Some Regions in Al-Tuz Salah Al-Din Governorate during Winter Season - Karar Samen Ali; Loqman Abdallah Ali (Genius Journals, 2022)
This study aims to assess the radioactivity of radon gas and the risks because of exposure to it and to calculate the annual effective dose ratesand the risks of lung cancer. Radon gas concentrations were measured in dwellings consisting of (14) houses in some areas of Tuz city during the winter season (January 1st to 1st March) in 2022, using the CR-39 nuclear trace detector. The results obtained from 14 sites in the city of Tuz Khurmatu showed that the lowest and highest concentrations recorded in site No. (3) (Akso neighborhood Tuz 2), and the highest concentration was recorded in site No. (5) (Tuz Al Tayyar District 2). While the other sites, the concentration of radon gas ranged between the two. The results showed that the lowest value of the effective radium content (CR) was recorded in site No. (3) was in site No. 5, with a 3 with a rate of 14.7 Bq.m-3, and the highest value of 45.4 Bq/m In addition, the lowest value of the balanced radon equivalent 3 . rate of 27.63. Bq/m ), and 3 concentration (ECC) was recorded in site No. (3) with a rate of Bq/m3 (5.88 Bq/m ) was recorded in site No. (5), with a rate of (11.05 of (18.16 Bq/m3 the highest values ). We also noticed that the lowest value of the annual equivalent dose in site No. Bq/m3 (3) was (0.37) msv/y and the highest value was( 1.14) msv/y in site No. (5), with an average of (0.69) mv/y
Keywords: highest; study; radioactivity; ratesand